The Effect of Using Contraceptives on The Nutritional Status of Woman of Childbearing Age - Istifadatul Ilmiya (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
Nutritional status during this period, especially in women of childbearing age, is influenced by several things, including the use of contraceptives. Side effects of using contraception include excess weight gain which can cause various diseases. Meanwhile, long-term impacts for families who do not use contraception can be in the form of increasing population, food and nutrition shortages, low education, lack of job opportunities, high birth and death rates. The aim of this study was to analyze the effect of contraceptive use on nutritional status in women of childbearing age. This research is an analytical observational study with a cross sectional design. The research sample consisted of 225 respondents using Eta Squared test data analysis. The results of the study show that contraceptive use has a positive and significant effect on nutritional status (p = 0.24), which means that the hypothesis is accepted if F count > F table (p = 0.05) at a certain probability. Suggestions for future researchers are to pay attention to other factors so that the nutritional status of women of childbearing age remains normal even though they use contraception